LOCUS OF CONTROL INTERNAL DAN KEMATANGAN KARIR PADA SISWA SMA DAN SMK - Pujianti, Syifa (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2017)
This study aims to determine the relationship between internal locus of control with career maturity in high school and vocational students. This research uses quantitative method with correlational research design. The subjects of this study were 30 students of class X, X1, XII from SMK Karya Guna 1, SMAN 10 Kota Bekasi and SMK Patriot Bekasi. The sampling technique used incidental sampling technique. Data collection using interviews, observation, and questionnaires. The questionnaire used is a questionnaire of career maturity and internal locus of control questionnaire. Data were analyzed using pearson product moment correlation.